Penal and Social Aspects of Water Theft: A Case Study of Ternate City - Faisal, Faisal; Lengkong Weku, Robert; Budiono, Arief; Mateo Ramon, Tomás (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
There are many cases of water theft from the Regional Drinking Water Company, especially in Ternate City. Article 28 letter h Regional Government of Ternate City No. 28 of 2011 on the Drinking Water Service of the Ternate City Municipal Water Company prohibits taking drinking water directly from distribution pipes or service pipes without going through a water meter. This research to analyze legal efforts against criminal acts of theft of Drinking Water Company Ternate City water committed by customers and non-subscribers through criminal and social efforts. This empirical research uses a statutory approach and a case approach. The results showed legal prevention of criminal acts of water theft can be done through penal efforts emphasizing repressive efforts (suppression/ eradication/extermination) and non-penal efforts emphasizing social and community efforts (prevention/anticipation/control). It is expected that the combination of criminal sanctions and social sanctions is expected to reduce the rate of water theft.